Schulzowskie rysowanie. Artystyczne persyflaże i powinowactwa - Kossowska, Irena (Sztuka i Kultura, 2016)
The text concentrates on interpretative context in which the artistic oeuvre of Bruno Schulz can be perceived, both with regard to dialogue of the artist with the culture of past centuries, and to his contemporary affiliations and relationships. Humour, ironic and self-ironic distance, the glance of a goodnatured taunter encompassing both the common reality of the home province of Drohobycz, and the centuries-old cultural tradition of mankind were the ways in which Schulz searched for the essence of being, tried to apprehend the original sense of notions and phenomena, and fathom the mystery of existence underlying the collective unconsciousness of dozens of generations. Irony, pan-irony, pan-masquerade, world turned upside down – those methods are not new; they have been masterly seized upon by the romantics and their spiritual heirs in order to tame the anxiety towards the incomprehensible, to alleviate the existential despair, and to ignore the toils of the temporal. In this respect, Schulz may be defined as an outstanding neo-romantic, creative, original and one of a kind successor to the aforesaid attitude. The analysis of unconsciousness, typical for the generation fervently ingesting the writings of Freud and Jung, parodical intentions and extolment of ugliness link Schulz furthermore to the current in Polish modernism represented by works of Witold Wojtkiewicz, Stanisław Ignacy Witkiewicz and Roman Jaworski. Constructing his own private mythology from “shreds of sculptures and statues of gods”, Schulz reached out for diverse elements of the cultural heritage, extracting them both from antique mythologies and from myths closer in time, which he comprehended as “transformed, mutilated and transmuted” versions of the primeval beliefs and treated as deformed and fragmentary incarnation of the original sense. One contemporary myth of special meaning to the artist was Stanisław Przybyszewski’s theory of antinomy of the sexes, inspired by Schopenhauer: the concept of a demonic woman destroying man in order to provide for the continuity of the human race. The topos of satanic female, seen as in distorting mirror, paraphrased, became the keynote of Schultz’s drawn and graphic oeuvre; his Xięga Bałwochwalcza (Idolatry Book) from 1920–1922 is devoted to it. This album contained in germinal form ideas and motives as well as pictorial precognitions of what the artist would present several years later in the form of hallucinatory literary depictions in his stories with multilevel symbolism. Schulz – insomuch as Wojtkiewicz and Witkiewicz, who parodied the canons of the “metaphysics of sex” - was not able to liberate himself from erotic phobias, but he defused this dramatic tension with irony and lowering the pathetic tone with regard to the cult of femininity professed by him. The artist perceived erotic perversion as a starting point for creating a poetic and philosophical parable. The aspect of artistic indeterminacy was brought forward by Schulz by evoking old masters’ art in composition schemes and titles of his prints; pastiches and travesties of paintings by Titian, Velazquez and Goya, by the authors of Rococo fetes galantes and symbolic oneiric depictions served both deciphering of the primeval sense concealed in myths and Biblical motives, and accentuating centuries-old cultural stratifications inherited by contemporary civilization. For Schulz, who blended together ingredients of everyday reality, products of own imagination and elements of bygone cultures into a homogeneous unity in a masterly way, the revolutionary demands of the 20th century “-isms” must have appeared profoundly misguided. With regard to this, his stance may be compared, by the way, with the currents of new realism, emerging in the 1920’s and gradually overbearing the doctrines of radical avant-garde. The artist, while being a belated modernist, was also a child of his time. On the one hand, the hallucinatory pictorial chains which he employed in his literary stories dovetail the experiences of surrealists searching for hidden contents of individual and collective unconsciousness; on the other, his drawings display characteristics akin to Italian metaphysical painting. Furthermore, researchers pointed out Schultz’s affinity with Balthus who evoked in his representations of a nymphette the atmosphere of pervert eroticism, and wrote about his fascination with the painting of Ignacio Zuloaga, as well as with the phantasmagoric drawings by Alfred Kubin. On top of that, Debora Vogel noticed a kinship of Schultz’s poetics with the oeuvres of two representatives of German Neue Sachlichkeit, Otto Dix and Georg Grosz. In spite of the fact that the art of Schulz kept its idiosyncratic position in the context of European culture of the interwar period, it can not go unheeded that problems disconcerting the generation of artist contemporary with him are well reflected in it. In building his creative vision, Schulz based on percipient observation of his surroundings in Drohobycz, its provincial scenery and people close to him: relatives, friends and acquaintances, whose features he immortalised in drawings and in prose. Anchored in everyday reality and in dreariness, he evoked in his syncretic imagination old myths and topoi in European art, based on them, in order to transform his observations creatively, combine them into a new unity, give them new form and new sense. His art, seemingly realistic, in fact displays a telling loosening of the “tissue of reality”, the “bankruptcy of reality”, be it empirical, social, or historical, in order to achieve the alternative reality of “personal, private mythology”.